A Diaminoterephthalate–C60 Dyad: A New Material for Optoelectronic Applications - Freimuth, Lena; Rozzi, Carlo Andrea; Lienau, Christoph; Christoffers, Jens (Synthesis, 2015)
Diaminoterephthalate was used for the first time as a chromophore in a dyad with [60]fullerene. The synthesis was accomplished from the benzyl methyl diester by hydrogenolytic cleavage of the benzyl group, re-esterification with a benzyl alcohol with protected formyl function, deprotection of the latter and final 1,3-dipolar cycloaddition with C60 and sarcosine via the azomethine ylide.
Keywords: diaminoterephthalate; 1,3-dipolar cycloaddition; dyad; esterification; fullerene